No games to watch: empirical analysis of sport fans` stress and coping strategies during COVID-19 lockdown - Kwon, Y.; Kwak, D.H. (International Journal of Sports Marketing & Sponsorship, 2021)
Purpose: The global outbreak of the COVID-19 forced most sport leagues to cancel games in March-April 2020, leaving no sport games to watch for sport fans. The present study examined how sport consumers appraise stress and engage in coping behaviors resulted from sport lockout due to the global pandemic. Design/methodology/approach: This study examined the relationship between sport fans` psychological dispositions, threat appraisal and coping strategies among professional sport fans in the USA. A panel of sport fans (N = 446) representative of the US adult population participated in an online survey in the fourth week of April, 2020 when no major sport leagues made a return from the lockout due to the COVID-19 outbreak. Findings: Results of this present study showed that anger, aggressiveness and need for affiliation increased threat perceptions toward the COVID-19 lockout, which subsequently had significant effect on emotion-focused and disengagement coping behaviors. Research limitations/implications: This is the first empirical study that examined stress and coping behavior among sport fans in the global public health crisis context. Our findings show what triggers stress appraisals and how fans cope with them. Practical implications: Findings suggest that segmenting sport fans based on psychological dispositions could be useful in predicting fans that will engage in coping behaviors. Social implications: While the hope is to return to normal postpandemic, COVID-19 might not be the last. We are uncertain whether there might be another potential pandemic-related sport lockdown. Understanding how lack of sport events can create distress in sport fans and have important public health implications. Originality/value: The findings provide empirical evidence on how sport consumers respond to the pandemic-related sport lockdown and cope with the unprecedented situation. The findings of this study contribute to the sport management literature as we are unsure whether the sport industry might face this challenging situation in the future again.